Anatomy : Descriptive and Surgical - Gray, Henry, 1825-1861; Edited by Pick, T. Pickering 1841-1919 and Howden, Robert, 1856- (New York Bounty Books)
"Gray's Anatomy is a landmark medical text. Illustrated with more than 500 clinical drawings and comprehensively indexed, it is considered one of the most historically important studies of human anatomy ever published."
Include Index
Keywords: Human anatomy -- Anatomy -- Anatomy, Surgical and topographical